2016
DOI: 10.3390/molecules21040480
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constituents of Medicinal Plants with Activity against Trypanosoma brucei

Abstract: Neglected tropical diseases (NTDs) affect over one billion people all over the world. These diseases are classified as neglected because they impact populations in areas with poor financial conditions and hence do not attract sufficient research investment. Human African Trypanosomiasis (HAT or sleeping sickness), caused by the parasite Trypanosoma brucei, is one of the NTDs. The current therapeutic interventions for T. brucei infections often have toxic side effects or require hospitalization so that they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Vanillic acid ( 3 ) is a hydroxybenzoic acid derivative belonging to the class of phenolic compounds. These natural compounds have been particularly studied for their potential as anti‐parasitic agents . Although no effectiveness against L. infantum intracellular amastigotes could be observed in our assays, previous studies demonstrated the antiparasitic effect of vanillic acid ( 3 ).…”
Section: Resultsmentioning
confidence: 77%
“…Vanillic acid ( 3 ) is a hydroxybenzoic acid derivative belonging to the class of phenolic compounds. These natural compounds have been particularly studied for their potential as anti‐parasitic agents . Although no effectiveness against L. infantum intracellular amastigotes could be observed in our assays, previous studies demonstrated the antiparasitic effect of vanillic acid ( 3 ).…”
Section: Resultsmentioning
confidence: 77%
“…This disease is transmitted by tsetse fly (genus Glossina ), a vector which is only found in tropical Africa, this explains the T. brucei geographic restriction [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the African flora represents a valuable source of anti-infectious compounds to be exploited as drugs [ 5 , 6 , 7 ]. In the fight against Trypanosoma infections, new therapeutic options can be provided by plant extracts, essential oils, and plant-borne compounds [ 6 , 8 , 9 , 10 ]. Essential oils are volatile mixtures distilled from aromatic plants and composed of several dozens of components such as terpenoids, phenylpropanoids, and aliphatic compounds [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%